Exploring the Efficacy of Early Intervention Strategies for Stroke Patients in The Emergency Department - Ahmed Yahya Ahmed Khormi , Abdulrahman Hussain Tayyib Rajhi , Muneer Abdullah Hussain Ageeli , Abdullah Ibrahim Hassan Mahdi , Khalid Alhabib Muni Alhelali , Mohmmed Ahmed Atyah Grhadi; Waleed Essa Mohsin Kohrmi , Yahya Ahmed Madkhali , Abbas Mohammad Ali Hakami , Ahmed Abdu Ahmed Qumayri , Abdu Ibrahim Muhammed Khardali , Raad Ibrahim Ahmed Muqri (Migration Letters, 2022)
Stroke is the second leading cause of death and a major cause of disability worldwide. Every year, 15 million people suffer a stroke globally, of which 5 million die and another 5 million are permanently disabled. The emergency department (ED) plays a pivotal role in the early management of stroke patients. A number of strategies have been employed to expedite stroke care in the ED, but their efficacy remains unclear. This review aims to review the literature on early intervention strategies for stroke patients in the ED and evaluate their impact on key outcomes. A systematic search of PubMed, Embase, CINAHL, and Cochrane Library was conducted from inception to January 2022. The search terms used were "stroke" AND "emergency department" OR "accident and emergency" AND "intervention" OR "strategy" OR "pathway" OR "team" OR "protocol" OR "bundle" OR "telemedicine" OR "pre-hospital" OR "notification". Studies were included if they: 1) evaluated an ED-based intervention for acute stroke, 2) reported on process measures (e.g., door-to-needle time), clinical outcomes (e.g., mortality, functional status), and/or cost-effectiveness. Studies were excluded if they: 1) were reviews, letters or case reports, 2) lacked a control or pre-intervention group for comparison. A total of 567 articles were identified, of which 23 studies met the eligibility criteria. Fifteen studies evaluated the impact of stroke teams/protocols/care bundles in the ED. Nine of these reported a significant reduction in door-to-needthrombolysis time. Six studies showed improved clinical outcomes with lower mortality and higher rates of independent ambulation at discharge. Eight studies assessed telemedicine for stroke. All reported reduced door-to-needle times, with mean reductions ranging from 13-38 minutes. Five studies found lower mortality rates with telemedicine. Two studies evaluated the effect of pre-hospital notifications. Both showed significantly shorter emergency assessment times. One found lower rates of in-hospital mortality. Future research should explore factors driving the observed disparities to reduce the enormous individual and societal burden of stroke worldwide. Overall, these findings indicate that implementing organized stroke care pathways has the potential to significantly enhance stroke care quality and outcomes. In summary, stroke teams/protocols, telemedicine, and pre-hospital notifications show promise as effective strategies for facilitating early intervention for stroke patients presenting to the ED. Their implementation holds implications for reducing treatment delays, mortality, and disability from stroke on a large scale. Wider adoption of these approaches should be encouraged to optimize acute stroke management.